Literasi Digital untuk Peningkatan Kapasitas 'Aisyiyah melalui Canva, Media Sosial, Google Forms, dan Artificial Intelligence - Ida Untari; Mar’atul Azizah Zahro; Arif Nugroho Hernanjaya; Anisa Eka Wulandari; Ketrin Anas Tasya (ServeInnovate: Journal of Applied Community Engagement (SJACE), 2026)
The rapid development of digital technology requires community organizations to adapt, including 'Aisyiyah, which plays a strategic role in Islamic da’wah and community empowerment. This community service program aimed to enhance the digital literacy capacity of 'Aisyiyah leaders and administrators in Surakarta to support more professional, effective, and modern organizational management. The program was implemented through five structured phases: needs assessment, hard-skills training, soft-skills and strategic capacity building, mentoring, and evaluation. The training was conducted on May 2, 2026, at the CBT Laboratory of Universitas Muhammadiyah PKU Surakarta and was attended by 47 participants representing the regional board, councils, institutions, and branch offices of 'Aisyiyah across Surakarta. The evaluation results demonstrated an improvement in participants’ knowledge, as reflected in the increase in the mean score from 87.80 in the pre-test to 96.11 in the post-test, representing a 7.64% increase. In addition, 67.5% of participants rated the program as excellent. The outputs of the program included digital posters, online forms, AI-assisted content, media publications, activity videos, and a Digital Literacy Training Module that obtained copyright registration (Registration No. EC002026065425). Overall, the program successfully strengthened participants’ digital literacy competencies and supported the acceleration of organizational digital transformation to enhance 'Aisyiyah’s da’wah and community empowerment activities in the digital era.